Comparison of a Rule-Based Algorithm with a Phenotype-Based Algorithm for the Interpretation of HIV Genotypes in Guiding Salvage Regimens in HIV-Infected Patients by a Randomized Clinical Trial: The Mutations and Salvage Study - Gianotti, Nicola; Mondino, Vincenzo; Rossi, Maria Cristina; Chiesa, Elisabetta; Mezzaroma, Ivano; Ladisa, Nicoletta; Guaraldi, Giovanni; Torti, Carlo; Tarquini, Pierluigi; Castelli, Paula; Di Carlo, Aldo; Boeri, Enzo; et al. (Clinical infectious diseases, 2006)
Background. There is still considerable uncertainty as to the best algorithm for interpreting human immunodeficiency virus (HIV) genotyping results. Methods. A total of 318 subjects with HIV RNA levels of >1000 copies/mL were enrolled in 41 centers throughout Italy from 2001 through 2003, stratified on the basis of their drug history, randomized (1 : 1) to 2 arms to have their treatments modified on the basis of the results of HIV genotyping (as interpreted by virtual phenotype analysis or with use of a rule-based interpretation system), and followed up for 48 weeks. At least 1 nucleoside reverse-transcriptase inhibitor and 1 protease inhibitor had to be included in any new regimen; nonnucleoside reverse-transcriptase inhibitor—naive patients were also prescribed a nonnucleoside reverse-transcriptase inhibitor. Only drugs licensed in Italy were allowed. The primary end point was a decrease in HIV RNA level to <400 copies/mL by week 12 according to on-treatment analysis. Results. The mean (± standard deviation) values at baseline were as follows: HIV RNA level, 4.1 ± 0.74 log10 copies/mL; CD4+ T lymphocyte count, 410 ± 262 cells/µL; reverse-transcriptase mutations, 4.8 ± 2.9; and protease mutations, 2.8 ± 2.5. There were 133 patients (41.8%) who were nonnucleoside reverse-transcriptase inhibitor naive and protease inhibitor experienced, 63 patients (19.8%) who were nonnucleoside reverse-transcriptase inhibitor experienced and protease inhibitor naive, and 122 patients (38.4%) who were 3-class experienced. A total of 192 patients completed 12 weeks of the treatment regimen assigned at baseline; at 12 weeks, 66.3% of patients in the virtual phenotype arm and 71.3% of patients in the rule-based interpretation arm had HIV RNA levels of <400 copies/mL (P = .46). No statistically significant difference between arms was observed by intention-to-treat analysis. Conclusion. Both the virtual phenotype and rule-based interpretation methods of HIV genotyping can guide the selection of effective antiretroviral drugs for a salvage regimen.